On a Slightly Different Power Law-Scaling for the Flat Universe - Sivakumar, C.; Francis, R. (Journal of Scientific Research, 2020)
A slightly different power law-scaling fits to the picture of our 13.7 billion years old flat universe which is expanding presently at 67 km/s/Mpc with an acceleration. The model which is an attempt to retain power-law scaling in the light of the accepted facts about the universe we are living in, has a constant effective equation of state parameter as the cosmic fluid is a solution of matter, radiation and dark energy. It is successful in explaining the acceleration of universe which the normal power law fails if the present Hubble parameter is 67 km/s/Mpc and age of the universe is 13.7 billion years, and it is free from the defect of singularity.